A diagnostic dilemma: drug-induced aseptic meningitis in a 45-year-old HIV-positive man. (March 2014) - Rowley, D; Houlihan, L; McFaul, K; Clarke, S; Lyons, F
We describe a case of aseptic meningitis following the administration of moxifloxacin in a 45-year-old man with human immunodeficiency virus (HIV). At presentation he was receiving tuberculosis treatment on a modified regimen following severe hepatotoxicity; this included moxifloxacin, started 8 days previously. Initial cerebrospinal fluid (CSF) analysis was grossly abnormal. Anti-viral and -bacterial treatments were started. All microbiological tests proved negative and his moxifloxacin was withheld resulting in a complete normalisation of CSF. Drug-induced aseptic meningitis is a diagnosis of exclusion and presents a serious diagnostic dilemma. The decision to withhold medication cannot be taken lightly.